Peaty wetlands of the Nahuelbuta National Park (Araucanía Region), compared with others in a latitudinal Chilean gradient Humedales turbosos del Parque Nacional Nahuelbuta (Región de la Araucanía) comparados con otros, en un gradiente latitudinal de Chile - Ramírez, Carlos; Valenzuela, Jorge; Vidal Ojeda, Osvaldo Javier; Fariña, José Miguel; Martín, Cristina San; Marticorena, Alicia; Valdivia, Oliver (My University, 2023)
Peat bogs are wetlands characterized as swamps of very extreme cold and wet places. In Chile there are several types of them: sphagnum bogs (minerotrophic), pulvinated bogs (ombrotrophic), grassy bogs, shrubby bogs and wooded bogs. This work was carried out in the peat bogs of the northern limit of them areal, in Nahuelbuta National Park, located in the Cordillera de la Costa approximately 1200 to 2300 m above sea level between the Regions of Bío-Bío and Araucanía, Chile. The flora was studied with traditional methods and the vegetation with phytosociological methodology and the results were confirmed with multivariate classification and ordination statistics. The vascular, moss and lichenic flora showed little floristic richness, only 38 species. All the flora species are native and six of them are endemic. This flora gives rise to four new peaty plant associations for Chile: two pulvinate-bogs (Myrteolo-Donatietum fasciculariae and Gaultherio-Oreoboletum obtusangulae), one sphagnum-bogs (Carici-Sphagnetum magellanicii) and one grassy-bogs (Bacharido-Festucetum scabriusculae). When comparing the peat bogs studied with those further south, the donatia pulvinate-bogs appear to be more homogeneous than the sphagnum peat bogs, in fact, the former share five species and the latter, only two. In general, a greater variation of the pulvinated peat bogs was found in the Aysén Region and of the sphagnum bogs in the Chiloé Region, the latter coming out of the conglomerate formed by the other four places. It was confirmed that in both latitudinal extremes the peat bogs are poorer in species and the greatest richness occurs in the intermediate regions.
Keywords: flora; latitudinal gradient; multivariate statistic; peat bogs; vegetation